Isolation, Screening, and Molecular Identification of Cellulolytic Bacteria From Supit Urang Municipal Landfill, Malang City: Identification of Cellulolytic Bacteria From Supit Urang Municipal Landfill - Maghfira Selia; Irfan Mustafa; Farida Rahayu (Journal of Tropical Life Science, 2024)
The municipal landfills contain substantial amounts of lignocellulosic waste that have not been adequately utilized. This waste can be processed using cellulolytic bacteria. Cellulolytic bacteria play an important role in the degradation of cellulose-based materials. This study aimed to isolate and identify cellulolytic bacteria based on 16S rDNA sequence obtained from the Supit Urang municipal landfill, Malang City. Bacteria were isolated from soil by cultivating on 1% carboxyl methyl cellulose (CMC) agar media. The cellulolytic activity was analyzed semi-quantitatively with flooded 1% Congo red and then washed with 1 M NaCl three times. Cellulase activity assay was measured using the 3.5-Dinitrosalicylic Acid (DNS) method. The most potential isolate in cellulose decomposition was identified. The most potential isolate in cellulose decomposition was identified. Twenty isolates of cellulolytic bacteria were obtained from the sample and sixteen isolates formed the clear zone. The cellulolytic index ranged between 0.26 and 1.52. Five isolates, SL1, SL2, SL10, SL16, and SL19 had the highest cellulolytic index. Isolate SL2 had the highest cellulase activity at 0.071 U/mL. Based on the 16S rDNA sequence, SL2 was identified as Bacillus amyloliquefaciens F98 with a similarity of 99.02%. This potential isolate has prospects for the biodegradation process from agricultural waste, which can be processed into valuable products.